Monoclonal antibodies for prophylaxis and therapy of respiratory syncytial virus, SARS-CoV-2, human immunodeficiency virus, rabies and bacterial infections: an update from the World Association of Infectious Diseases and Immunological Disorders and the Italian Society of Antinfective Therapy - Esposito, Susanna; Amirthalingam, Gayatri; Bassetti, Matteo; Blasi, Francesco; De Rosa, Francesco Giuseppe; Halasa, Natasha B.; Hung, Ivan; Osterhaus, Albert; Tan, Tina; Torres, Juan Pablo; Vena, Antonio; Principi, Nicola (Frontiers in Immunology, 2023)
Monoclonal antibodies (mABs) are safe and effective proteins produced in laboratory that may be used to target a single epitope of a highly conserved protein of a virus or a bacterial pathogen. For this purpose, the epitope is selected among those that play the major role as targets for prevention of infection or tissue damage. In this paper, characteristics of the most important mABs that have been licensed and used, or are in advanced stages of development for use in prophylaxis and therapy of infectious diseases are discussed. We showed that a great number of mABs effective against virusor bacterialinfections have been developed, although only in a small number of cases these are licensed for use in clinical practice and have reached the market. Although some examples of therapeutic efficacy have been shown, not unlike more traditional antiviral or antibacterial treatments, their efficacy is significantly greater in prophylaxis or early post-exposure treatment. Although in many cases the use of vaccines is more effective and cost-effective than that of mABs, for many infectious diseases no vaccines have yet been developed and licensed. Furthermore, in emergency situations, like in epidemics or pandemics, the availability of mABs can be an attractive adjunct to our armament to reduce the impact. Finally, the availability of mABs against bacteria can be an important alternative, when multidrug-resistant strains are involved.